Maternal vitamin D status in type 1 diabetic pregnancy: impact on neonatal vitamin D status and association with maternal glycaemic control. - Sarah E Bennett; Jennifer McPeake; David R McCance; John G Manderson; Philip Johnston; Rachel McGalliard; Ann McGinty (PLoS ONE, 2013)
Objective The first aim of this study was to assess 25-hydroxy vitamin D (25OHD) concentrations in women with type 1 diabetes (T1DM) during pregnancy, post-delivery and also foetal (cord blood) 25OHD concentrations and to examine relationships between these. The second aim of the study was to investigate potential interactions between maternal body mass index (BMI) and foetal vitamin D status. A further study aim was to examine potential relationships between maternal 25OHD and glycosylated haemoglobin (HbA1c) throughout pregnancy. Research design and methods This was an observational study of 52 pregnant controls without diabetes and 65 pregnant women with T1DM in a university teaching hospital. Maternal serum 25OHD was measured serially throughout the pregnancy and post-delivery. Cord blood 25OHD was measured at delivery. 25OHD was measured by liquid chromatography tandem mass spectrometry (LC-MS/MS). Results Vitamin D deficiency (25OHD <25 nmol/L) was apparent in both the T1DM subjects and controls at all 3 pregnancy trimesters. Vitamin D levels in all cord blood were <50 nmol/L. Maternal 25OHD correlated positively with cord 25OHD at all 3 trimesters in the T1DM group (p=0.02; p<0.001; p<0.001). 25OHD levels within cord blood were significantly lower for women with diabetes classified as obese vs. normal weight at booking [normal weight BMI <25 kg/m(2) vs. obese BMI >30 kg/m(2) (nmol/L ± SD); 19.93 ± 11.15 vs. 13.73 ± 4.74, p=0.026]. In the T1DM group, HbA1c at booking was significantly negatively correlated with maternal 25OHD at all 3 trimesters (p=0.004; p=0.001; p=0.05). Conclusion In T1DM pregnancy, low vitamin D levels persist throughout gestation and post-delivery. Cord blood vitamin D levels correlate with those of the mother, and are significantly lower in obese women than in their normal weight counterparts. Maternal vitamin D levels exhibit a significant negative relationship with HbA1c levels, supporting a potential role for this vitamin in maintaining glycaemic control.